2010
DOI: 10.1590/s0102-695x2010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical studies on tubers of Momordica tuberosa Cogn., Cucurbitaceae

Abstract: RESUMO: "Estudos farmacognósticos de tubérculos de Momordica tuberosa Cogn., Cucurbitaceae". Este trababalho teve como objetivo estabelecer um perfil farmacognóstico dos tuvérculos da planta Momordica tuberosa Cogn., Cucurbitaceae. A morfoanatomia dos tubérculos da espécie foi realizada para estabelecer um perfil completo que possa ajudar na identificação e evitar problemas na sua taxonomia. Os ensaios foram realizados usando microscópio ótico, procedimentos fisico-químicos e fitoquímicos estabelecidos pela OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…revealed a convex outline on the adaxial surface and triangular outline on the abaxial surface. 35 About the presence of collenchyma in the petiole, this tissue has also been observed in B. alba and some species of Momordica. 36 In the latter case, Aguoru and Okoli have verified that the number of collenchyma layers can be a character to differentiate them.…”
Section: Discussion/ Conclusionmentioning
confidence: 79%
“…revealed a convex outline on the adaxial surface and triangular outline on the abaxial surface. 35 About the presence of collenchyma in the petiole, this tissue has also been observed in B. alba and some species of Momordica. 36 In the latter case, Aguoru and Okoli have verified that the number of collenchyma layers can be a character to differentiate them.…”
Section: Discussion/ Conclusionmentioning
confidence: 79%
“…also has a triangular outline on the abaxial surface, but on the adaxial surfaceit has a convex outline. 37 Sãvulescu and Hoza 38 observed that the cuticle is thin in the petiole of M. charantia, while Coutinho et al 39 described the cuticle as slightly thickened. The presence of collenchyma in the petiole may be a useful feature to distinguish species of Momordica.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…In M. tuberosa, the palisade parenchyma presents two layers of cells and the idioblasts are inserted in both surfaces of the epidermis, 37 making these characters useful for differentiation of M. charantia. Analyzing the powder of the leaf blade of M. tuberosa, Kumar et al 37 cited that the idioblasts appear in pairs or, occasionally, in groups of more than three idioblasts. They were not found in the literature histochemical studies with leaves of M. charantia.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The roots are woody, tuberous and perennial. 2 It contains several phyto-constituents such as sterols, saponins, triterpenoids, cardiac glycosides, flavonoids, carbohydrates. 2 The medicinal properties of various parts of M. tuberosa are testified.…”
Section: Introductionmentioning
confidence: 99%
“…2 It contains several phyto-constituents such as sterols, saponins, triterpenoids, cardiac glycosides, flavonoids, carbohydrates. 2 The medicinal properties of various parts of M. tuberosa are testified. It possess antidiabetic, hypolipidemic, 3 antiovulatory, abortifacient, 4 antidiarrhoeal, 5 anticonvulsant, 6 antioxidant, hepatoprotective, 7 nephroprotective, 8 antidepressant, 9 antiulcer 10 properties.…”
Section: Introductionmentioning
confidence: 99%